Effect of titania on the microstructure evolution of sintered magnesite in correlation with its properties. Issue 7 (August 2015) - Kumar, P.; Burhanuddin,; Kumar, A.; Ghosh, A.; Sinhamahapatra, S.; Tripathi, H.S.
Abstract: Natural Indian magnesite contains large amount of impurities like CaO, SiO2 and Fe2 O3 . On heat treatment, these impurities chemically react and form low melting phases like monticellite (CMS), merwinite (C3 MS2 ) and vitreous phases, which degrade the refractory properties of magnesite like hot modulus of rupture, corrosion resistance etc. In the present investigation, TiO2 was used to reduce the formation of low melting phases. Compacted green pellets and bars of magnesite containing 0−5 wt% TiO2 were sintered in the temperature range of 1500−1600 °C with 2 h soaking at peak temperature. It was observed that TiO2 slightly increased the apparent porosity and decreased the bulk density by reducing the formation of low melting phases. High temperature flexural strength increases with TiO2 content upto 3 wt% followed by slight decrease in strength after further increase in the amount of additive.